JURIDICAL ANALYSIS ON BIPARTITE NEGOTIATION IN THE EMPLOYEE TERMINATION PROCESS AT PT. J RESOURCES BOLAANG MONGONDOW, INDONESIA - Theresa B. Tulende; Hosiana D. A. Gultom; Agus Budianto (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2021)
The disputes over termination of employment are common in the industrial relations. Many industrial relations actors settle disputes by filing lawsuits to the Industrial Relation Court. They assume that bipartite negotiation is ineffective in settling disputes of termination of employment in particular. In contrary, a company In Indonesia, named PT. J Resources Bolaang Mongondow, experiences it differently where the bipartite negotiation is well-emphasized in settling disputes of termination of employment. This is also supported by various strategies implemented inside the company to prevent any disputes, particularly the termination of employment that leads to the Industrial Relation Court. This paper uses descriptive analysis as well as normative-empirical legal as the research method. The data was collected through literature review, research papers, essays, national journal, interview, website as well as legal studies. The termination of employment is regulated under Law No. 13 of 2003 concerning Manpower, while the Law No. 2 of 2004 regulates the Industrial Relations Dispute Settlement. Likewise, the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia No. PER.31/MEN/XII/2008 concerning the Guideline for Settlement of Industrial Relations Dispute through Bipartite Negotiations. The disputes of termination in industrial relations emerge due to the violation of company regulation in the employment contract done by the employee. Nonetheless, PT. J Resources Bolaang Mongondow has been successfully implementing the bipartite negotiations to settle disputes. Law No. 2 of 2004 concerning the Industrial Relations Disputes Settlement requires that it has to be resolved first through bipartite bargaining in deliberation to reach consensus. Strategy determines the effectiveness of bipartite negotiations in a company.